CTA's Question-and-Answer Service used to the full - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Vincent Zigirinshuti runs a small food processing factory in Rwanda, and when he wrote to CTA's Question-and-Answer Service, he was sent all information relevant to making powdered soya milk. Mr Zigirinshuti used this information to market a baby...